A Serial Mediation Model of Perceived Social Class and Cyberbullying: The Role of Subjective Vitality in Friendship Relations and Psychological Distress - Hadi Samadieh; Ahmad Khamesan (Iranian Journal of Psychiatry)
Objective: The link between individuals' perceptions of social class (PSC) and various forms of bullying, including cyberbullying, has not been extensively studied. Additionally, the mechanisms through which PSC impact aggressive behaviors like cyberbullying remain unclear. Therefore, this study aimed to explore the influence of perceived social class on cyberbullying, considering subjective vitality and psychological distress as serial mediators. Method: Utilizing a cross-sectional design, the research involved 584 Iranian students (Mage = 20.59, SD = 1.99) from several universities who completed questionnaires assessing Subjective Social Class (SSC), Subjective Vitality Scale (SVS), Psychological Distress Scale (K6), and Cyberbullying Involvement Scale (CIS). Hayes' PROCESS macro (Model 6) in SPSS was employed to analyze the chain mediation effects. Results: The Results demonstrated that the direct impact of PSC on cyberbullying was significant (Effect = -0.229, 95% CI: -0.294 to -0.164). Subjective vitality and psychological distress serially mediated the link between PSC and cyberbullying (Effect = -0.022, 95% CI: -0.035 to -0.012). In addition, both subjective vitality (Effect = -0.046, 95% CI: -0.080 to -0.017), and psychological distress (Effect = -0.09, 95% CI: -0.123 to -0.059), independently mediated the association between PSC and cyberbullying. Conclusion: This research not only broadens the theoretical understanding of how individuals' perceptions of their social rank influence cyberbullying behaviors, but also provides actionable strategies for officials and experts to deploy effective interventions in higher education to mitigate cyberbullying.